Re-interpreting the invisible boundaries of Bloemfontein: transforming the unconscious edges of familiarity into liminal spaces through architectural influences - Mojanaga, Ketumile (University of the Free State, 2019)
The dissertation was derived from a concept on the geographical analysis of the Bloemfontein context. The investigation came to a realisation that there are invisible boundaries in the city that are created by its residents/inhabitants. These boundaries are formed when the inhabitants primarily participate in specific segments of the city. This is often a result of the day-to-day needs which are sustained by utilities including stores, filling stations, markets, etc. The city is divided into various communal districts, to distinguish between sectors and to aid orientation. Today, 54 percent of the world’s population occupies urban development globally. A proportion expected to increase to 66 percent by 2050 (United Nations, 2014). Concurrently, this particular phenomenon increases the vehicular use in the city context and consequently affects traffic cascade and efficiency. The effortlessness of daily commute around and within a city has a considerable effect on its participation, tourism enticement, daily enterprise and the quality of life. Bloemfontein has established a commuter bus system that assists the daily transitions of its dwellers. However, the system has not adapted to modern-day transit. With the increased automotive transport in the city, the roads have gained congestion since the inception of the system and have therefore lengthened the process of moving from point A to point B. Secondly, the city appreciation and unique experience have depreciated over the years, primarily due to the constraints of vehicle manoeuvre. This escalating phenomenon eliminates the narrative the city can tell, relinquishing the precious gems of Bloemfontein. With regard to the above-mentioned scenarios, the dissertation proposes a Bus Rapid Transit system. Utilising this type of system, the citizens can discover other parts of the city other than the ones they are familiar with. They can appreciate the visual treasures Bloemfontein offers, in the comfort of a transit system.
Dissertation (M.Arch. (Architecture))--University of the Free State, 2019
Keywords: Architecture; Geographical analysis -- Bloemfontein; Urban design